Connections Matter: Channeled Hydrogels to Improve Vascularization - Muehleder, Severin; Ovsianikov, Aleksandr; Zipperle, Johannes; Redl, Heinz; Holnthoner, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2014)
The use of cell-laden hydrogels to engineer soft tissue has been emerging within the past years. Despite several newly developed and sophisticated techniques to encapsulate different cell types the importance of vascularization of the engineered constructs is often underestimated. As a result, cell death within a construct leads to impaired function and inclusion of the implant. Here, we discuss the fabrication of hollow channels within hydrogels as a promising strategy to facilitate vascularization. Furthermore, we present an overview on the feasible use of removable spacers, 3D laser- and planar processing strategies to create channels within hydrogels. The implementation of these structures promotes control over cell distribution and increases oxygen transport and nutrient supply in vitro. However, many studies lack the use of endothelial cells in their approaches leaving out an important factor to enhance vessel ingrowth and anastomosis formation upon implantation. In addition, the adequate endothelial cell type needs to be considered to make these approaches bridge the gap to in vivo applications.